Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# How do you solve the equation $3x + 6 = 3(x - 5)?$

Last updated date: 14th Jul 2024
Total views: 380.4k
Views today: 9.80k
Verified
380.4k+ views
Hint: In this solution first of all we will open the bracket on the right hand side of the equation and then will move all the terms on the left hand side of the equation. When you move any term from one side to another sign of the term also changes.

Complete step-by-step solution:
Take the given expression: $3x + 6 = 3(x - 5)$
Multiply the term and open the bracket on the right hand side of the equation.
$3x + 6 = 3x - 15$
Move all the terms on the left hand side of the equation from the right hand side of the equation. When you move any term from one side to another then the sign of the term also changes. Positive term becomes negative and negative term becomes positive.
$\Rightarrow 3x + 6 - 3x + 15 = 0$
Arrange like terms together.
$\Rightarrow \underline {3x - 3x} + \underline {6 + 15} = 0$
Like terms with equal value and the opposite sign cancel each other, simplify the above equation.
$\Rightarrow 6 + 15 = 0$
$\Rightarrow 21 = 0$
But in actual $21 \ne 0$and so the given equation has no solution.